Bismuth ferrite (BiFeO3) perovskite-based advanced nanomaterials with state-of-the-art photocatalytic performance in water clean-up. Issue 8 (5th July 2022) - Gulati, Shikha; Goyal, Kartika; Arora, Aryan; Kumar, Sanjay; Trivedi, Manoj; Jain, Shradha
Abstract : Bismuth ferrite nanohybrids as efficient photocatalysts for wastewater remediation against toxic azo dyes pollutants. Abstract : Nowadays, as we face a massive epidemic of water-borne diseases, it is essential to find effective techniques for treating wastewater. Against the drawbacks of conventional treatment methods such as the generation of a lot of sludge, photocatalytic decomposition appears to be an effective technology for the treatment of water against industrial wastewater, especially azo dyes and other organic pollutants. This fascinating technique solves two problems of humanity, water crises as well as environmental problems. In terms of capacities, bismuth ferrite nanoclusters appear to be an effective semiconductor material for the degradation of a wide range of dyes due to their acceptable frequency range, wide visible light absorption, and good stability. These properties are known to increase to a greater extent when thin sheets of bismuth ferrite are modified. This review summarizes in detail the limitations associated with the use of conventional methods, emerging techniques for photocatalyst degradation, perovskite structure of photocatalysts, degradation mechanisms, and modifications of bismuth ferrite nanoparticles to improve photocatalytic performance and characterization studies. Basically, the modification involves a doping technique, i.e., combining support materials, preparing heterojunctions, and creating oxygen vacancies. In addition, future challenges and prospects are presented to focus on an area that requires the special interest of researchers. Therefore, this review aims to provide an overview and contribute to knowledge on bismuth ferrite photocatalysts by summarizing the current state of research and providing information on efficient techniques to handle bismuth environments.